+0  
 
0
92
1
avatar

Solve the equation.

 

\(\begin{pmatrix} 1 & 1 & 0 \\ 1 & 0 & 1 \\ 1 & -1 & -1 \end{pmatrix}\begin{pmatrix} x \\ y \\ z \end{pmatrix} = \begin{pmatrix} 1 \\ -1 \\ 1 \end{pmatrix}\)

 May 17, 2021
 #1
avatar+121056 
0

x +  y   =   1       ⇒  x - 1  =  - y       (1)

x +  z   =  -1      ⇒  x + 1   = - z         (2)

x - y - z =  1       (3)

 

Sub (1)  and (2)  into  (3)

 

x + ( x  -1)  + ( x + 1)  =  1

3x = 1

x  =1/3

 

y  = 2/3

 

z = -4/3

 

 

cool cool cool

 May 17, 2021

49 Online Users